The fecundity of mathematical methods in economic theory - Brand, Heinz Willi (Dordrecht: D. Reidel Pub. Co., 1961)
The book covers the following: The Logical Distinction between two Types of Mathematical Method - Respectively Mathematical Presentation and Mathematical Operation; Attempted Operational Assessment of the Intellectual Economy due to using Mathematical Methods; Investigation of the Intelligibility of Mathematical Methods; and Critical Appraisal of the Accuracy of Mathematical Methods as applied to Economic Theory.
Bibliography: p. 50-23.
rpm 30/10/2017
Loans
Keywords: Economics, Mathematical; Economic theory